The Word in the Wilderness : Popular Piety and the Manuscript Arts in Early Pennsylvania - Ames, Alexander Lawrence, 1987- (Book collections on Project MUSE., 2020)
"Examines the history of Fraktur (illuminated religious manuscripts created and used by Pennsylvania Germans in the eighteenth and nineteenth centuries) and explores its role in early American popular piety and devotional culture"--